Batman '66. Vol. 1 - Parker, Jeff, 1966-; Case, Richard (2014)
"Put on your go-go boots and get ready to "Batusi" back to the Swingin' 60s as DC Comics reimagines the classic Batman TV series in comics form for the first time! These all-new stories portray The Caped Crusader, The Boy Wonder and their fiendish rogues gallery just the way viewers remember them"--
Keywords: Batman (Fictitious character) -- Comic books, strips, etc; Robin the Boy Wonder (Fictitious character) -- Comic books, strips, etc; Vigilantes -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Supervillains -- Comic books, strips, etc; Nineteen sixties -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Graphic novels